2002
DOI: 10.1034/j.1600-0536.2002.470108.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing capacity of some trimers in p‐tert‐butylphenol‐formaldehyde resin

Abstract: Contact allergy to p-tert-butylphenol formaldehyde resin (PTBP-F-R) is not rare. This resin consists of a large number of substances, most of which are still unknown. For diagnostic and preventive reasons the chemical identity of the sensitizers should be known, as well as their sensitizing capacities, cross-reaction patterns and presence in the environment. The aims of this study were to investigate the sensitizing capacities and potential cross-reacting patterns for 4-tert-butyl- 2,6-bis-(5-tert-butyl-2-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In a previous study we have shown that the sensitizing capacities of the trimers XIII, XIVa and XVIII are considerably lower than those of the dimers IX and X [17]. Animal studies and the present study suggest a possibility of lowering the elicitation and sensitization qualities of PTBP-F-R.…”
Section: Iupac) XIII Was Identified As 4-tert-butyl-26-bis-(5-tert-supporting
confidence: 53%
“…In a previous study we have shown that the sensitizing capacities of the trimers XIII, XIVa and XVIII are considerably lower than those of the dimers IX and X [17]. Animal studies and the present study suggest a possibility of lowering the elicitation and sensitization qualities of PTBP-F-R.…”
Section: Iupac) XIII Was Identified As 4-tert-butyl-26-bis-(5-tert-supporting
confidence: 53%
“…Two main allergens in the resin with high sensitizing capacity in guinea pigs have been isolated and described. [35][36][37][38][39][40] Elicitation studies in sensitized patients have demonstrated that these allergens play a vital role in contact allergy to PTBP-FR in humans. [41][42][43][44] The allergens are the dimers, 4-tert-butyl-2-(5-tert-butyl-2-hydroxy-3-hydroxymethyl-benzyloxymethyl)-6-hydroxymethylphenol and 4-tert-butyl-2-(5-tert-butyl-2-hydroxy-benzyloxymethyl)-6hydroxymethylphenol.…”
Section: Discussionmentioning
confidence: 99%
“…PTBP‐FR contains hundreds of compounds, which have not been comprehensively identified chemically. Two main allergens in the resin with high sensitizing capacity in guinea pigs have been isolated and described 35–40 . Elicitation studies in sensitized patients have demonstrated that these allergens play a vital role in contact allergy to PTBP‐FR in humans 41–44 .…”
mentioning
confidence: 99%
“…In investigations of p-tert-butylphenol-formaldehyde resins, a number of trimers have been identified. As weak sensitizers, 37 these show that oligomer oxidation products could be of importance in oxidation mixtures of compounds that are prone to polymerization. The present study shows that also potent sensitizers can be formed in polymerization reactions.…”
Section: Mechanism Of Autoxidation and Formation Of Identifiedmentioning
confidence: 99%